2009
DOI: 10.1080/17518420902739365
|View full text |Cite
|
Sign up to set email alerts
|

Virtual enriched environments in paediatric neuropsychological rehabilitation following traumatic brain injury: Feasibility, benefits and challenges

Abstract: A frequent consequence of traumatic brain injury (TBI) is a significant reduction in patients' cerebral activation/arousal, which clinicians agree is not conducive to optimal rehabilitation outcomes. In the context of paediatric rehabilitation, sustained periods of inactivity are particularly undesirable, as contemporary research has increasingly called into question the Kennard principle that youth inherently promotes greater neural plasticity and functional recovery following TBI. Therefore, the onus to crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 108 publications
0
15
0
Order By: Relevance
“…It also reduces BBB damage induced by surgical injury and diminishes apoptotic, neuronal death while also improving vascularisation in the same model [115]. In humans, successful assays show the benefits of enriched environments in the injured brain and identify the potential and challenges associated with implementing environmental enrichment in pediatric neuropsychological rehabilitation [116].…”
Section: Environmental Enrichmentmentioning
confidence: 99%
“…It also reduces BBB damage induced by surgical injury and diminishes apoptotic, neuronal death while also improving vascularisation in the same model [115]. In humans, successful assays show the benefits of enriched environments in the injured brain and identify the potential and challenges associated with implementing environmental enrichment in pediatric neuropsychological rehabilitation [116].…”
Section: Environmental Enrichmentmentioning
confidence: 99%
“…In consequence of this and a multitude of other investigations, the period of adolescence, which is characterized by elevated rates of brain plasticity, presents an important neurodevelopmental staging interval under the course of which brain and behavior sensitivity to environmental influence, restricted to greater or lesser degrees by epigenetic factors, is considered substantial (Darnaudery and Maccari 2008;Law et al 2009;Leo et al 2009. Marco et al (2010 have reported that both chemical (e.g., methylphenidate) and environmental (e.g., physical or social enrichment) interventions have the propensity to counteract Adriani et al 2006;Nithianantharajah and Hannan 2006;Navailles et al 2008;Pereira et al 2008;Zaias et al 2008;Penn et al 2009;Zakharova et al 2009) the detrimental effects of developments insults of prior origin (see Marco et al 2010 , Tables 1 and 2).…”
Section: Neurodevelopmental Staging In Adolescencementioning
confidence: 97%
“…The adolescence period consists also of marked brain development and maturation of the HPA axis during which glucocorticoids influence programming effects on neurocircuitry involved in learning and memory (McCormick and Mathews 2009). There is a plethora of evidence emphasizing the notion that the adolescent brain requires a great deal of further development to reach maturity with wide-ranging changes in the prefrontal cortex (PFC) and mesolimbic regions (Giedd et al 1999;Sowell et al 2001;Güroglu et al 2009;Johnson et al 2009;Stevens et al 2009). Sturman and Moghaddam (2010) have indicated that adolescent rats were more susceptible to the functional activation evoked by internal and external motivating factors (e.g., hunger, or, cue presence on perseveration) during the extinction of a previously rewarded operant behavior.…”
Section: Neurodevelopmental Staging In Adolescencementioning
confidence: 98%
“…The application of VR to neurocognitive assessment is considered by a growing body of researchers to be distinctively important because it represents the potential for more than a simple linear extension of existing computer technology for human use (Campbell et al, 2009;Carelli et al, 2009;Riva et al, 2004). For such researchers, it is important that VR does more than simply automate the paradigms of the past (Penn et al, 2009). Instead, virtual environments should provide a paradigm shift for the future.…”
Section: Virtual Environments and Veridicality: Potential Loss Of Expmentioning
confidence: 99%